Two new compounds from the fruiting bodies of Ganoderma philippii. Issue 3 (4th March 2018) - Yang, Shuang; Ma, Qing-Yun; Kong, Fan-Dong; Xie, Qing-Yi; Huang, Sheng-Zhuo; Zhou, Li-Man; Dai, Hao-Fu; Yu, Zhi-Fang; Zhao, You-Xing
Abstract: Two new compounds, philippin (1 ) and 3β, 9α, 14α-trihydroxy-(22 E, 24 R )-ergost-22-en-7-one (2 ), were isolated from the fruiting bodies of Ganoderma philippii . Their structures were elucidated on the basis of the spectroscopic technologies, including 1D and 2D NMR as well as MS. The bioassay of inhibitory activity against acetylcholinesterase (AChE) showed compound1 exhibited weak inhibitory activity against AChE. Abstract :